Safety culture : building and sustaining a cultural change in aviation and healthcare - Patankar, Manoj S., 1968- (Ashgate, 2012)
In Safety Culture: Building and Sustaining a Cultural Change in Aviation and Healthcare, the four authors draw upon their extensive teaching, research and field experience from multiple industries to describe the dynamic nature of a culture-change process, particularly in safety-critical domains. They use a "stories to numbers" approach that starts with felt experiences and stories of certain change programs that they have documented, then proceed to describe the use of key measurement tools that can be used to analyze the state of a change program. The book concludes with a descript